Association Of Red-Tip Of Pineapple Leaves With Nutrient Deficiency - Juva Rajah, Vijiandran (2007)

(untitled)
The red-tip of pineapple leaves which affected the Gandul variety was sighted in the early 1990’s in Peninsula Plantations, Simpang Renggam, Johore where it has been found that about 10% or more of its leaves starting from the tip had turned red. It was speculated that it was due to sulphur deficiency as a result of the change of nitrogen carriers from ammonium sulphate to urea. This study was carried out with three main objectives: (i) to investigate whether the red-tip problem is related to nutrient deficiency through Missing Element Experimental Technique and thus identify the nutrients that are involved, (ii) to investigate the effect of ammonium sulphate and urea as the nitrogen carriers on the red-tip of pineapple leaves and also the plant performance in terms of vegetative growth and fruit yield at field conditions and (iii) to examine and compare the cell structural differences between the normal (green) and infected (red-tip) part of the pineapple leaf from cv. Gandul The Missing Element experiment was carried out in the glasshouse to achieve the first objective while the second objective was achieved through a field experiment in Simpang Renggam, Johore. Further to the above experiments, the red-tip area and the green area of the leaves were also viewed under a Confocal and Transmission Electron Microscope to look for any differences between them at the cellular level which covered the third objective of the study. Visual observations of the plants from the first experiment could not reproduce the red-tip as found in Simpang Renggam for all treatments including plants treated without the input of sulphur though there was some occurrence of the red-tip in these plants at 150 days after planting (DAP). The deficiency symptom of other eliminated nutrients was mostly similar to that reported in literature and there were no similarities seen compared with the red-tip phenomenon. Vegetative growth variables studied from the destructive sampling carried out at 180 and 300 days after planting showed significant differences between treatments only at the later stage of plant growth, the second stage of sampling. The first experiment indicated that sulphur deficiency was not the primary cause for the occurrence of the red-tip phenomenon in the pineapple leaves. Plants grown in the field from both treatments, i.e. plants fertilised with ammonium sulphate as nitrogen fertiliser (Treatment 1, T1) and plants fertilised with urea as nitrogen fertiliser (Treatment 2, T2) did not show any significant differences between them in terms of vegetative growth, plant nutrient uptake, soil nutrient concentrations and yield. There were also no significant differences between T1 and T2 in the red-tip percentage at all sampling periods except one but further soil and plant nutrient analysis did not show any significant differences. Besides that, the uptake trend of the macro and micro nutrients was also not significant for both treatments and the levels had indicated healthy growth for both treatments. The sulphur and other nutrient concentrations for plant and soil were well above the critical point for deficiency to occur and the continuous occurrence of red-tip in plants treated with input of ammonium sulphate gave a doubt whether sulphur is the main cause of the phenomenon. The insignificant yield between the two treatments had further increased the doubt. The second experiment had further strengthened that the deficiency of sulphur is not the cause of the red-tip in the pineapple leaves. With the above findings, observations carried out using the Confocal Microscope of both the green and red-tip area of the pineapple leaves revealed the presence of some blockages in the phloem cells of the red-tip area which was not found in the green area. Further magnification of this area using the Transmission Electron Microscope revealed presence of some globular structures in the sieve element cells of the red-tip area similar to the infection of Mycoplasma Like Organisms (MLO). The presence of these structures had most likely blocked the movement of nutrients through sieve element cells thus causing the disintegration of chlorophyll to anthocyanin causing the red-tip of pineapple leaves. However further trials are needed to confirm this speculation. The study had given an understanding that the red-tip phenomenon is not caused by the deficiency of sulphur or any other plant nutrients but due to the presence of the globular structures in leave cells which may be MLO.